BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Aprillia, Sindy; Kalsum, Ummi; Hidayat, Randy (Balance : Jurnal Akuntansi dan Bisnis, 2023)
This study is to determine the effect of Operational Costs, Operating Income, and Capital Adequacy Ratio on Bank Profitability both simultaneously and partially. Data analysis used in this study is a quantitative analysis carried out through statistical tests, then using multiple linear regression data analysis techniques with 60 data samples consisting of 12 Islamic commercial banks in Indonesia in the period 2017 to 2021. The results show that there is a significant influence Operating Costs Operating Income, and Capital Adequacy Ratio to Profitability of Islamic Banks in Indonesia, partially only Operating Costs Operating Income has an effect while the Capital Adequacy Ratio does not affect Return On Assets.